Teknik Relaksasi Benson terhadap Penurunan Intensitas Nyeri pada Pasien Pasca Operasi Appendiktomi - Risqi Amelia Ajifadillah; Fahrun Nur Rosyid (Journal of Telenursing (JOTING), 2026)
This study aimed to analyze the effectiveness of the Benson Relaxation Technique in reducing pain intensity among post-appendectomy patients. The method used was a literature review with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. The results showed that out of 1,245 articles identified, 9 articles met the eligibility criteria and were included in the review. All selected studies demonstrated that the Benson Relaxation Technique was effective in reducing pain intensity among post-appendectomy patients. In addition to pain reduction, this intervention contributed to improved sleep quality, reduced anxiety levels, and enhanced patient comfort during the recovery period. In conclusion, the Benson Relaxation Technique is an effective non-pharmacological complementary intervention for pain management in post-appendectomy patients because it is easy to implement, safe, and beneficial for both the physical and psychological well-being of patients.                                                                   Keywords: Appendectomy, Benson Relaxation Technique, Literature Review, Non-Pharmacological Therapy, Postoperative Pain